P‐199: Late‐News Poster: Color Mismatches across Commercial Displays: Modeling the Effect of Observer Metamerism. Issue 1 (29th May 2019) - Xie, Hao; Farnand, Susan P.; Murdoch, Michael J.; Park, Jae Sung; Min, Byungseok
Abstract : Based on the model of individual color matching functions, the magnitudes of observer metamerism potentials across characterized commercial color displays were simulated. Then, the displays' spectral dissimilarities were translated into better interpretable measures, and the possibility of optimal average representative of color matching functions was analyzed.